Social aspects of the informal economy: evidence from EU countries - Sorina Emanuela ȘTEFONI; Iulian Viorel BRAȘOVEANU; Ionela BUTU (Theoretical and Applied Economics)

(untitled)
Constantly developing, the informal economy continues to find new areas and directions of expansion, leading states to a position of constant search for solutions to temper it. The agricultural sector, the social one, and the rural areas are analyzed in this paper in relation to the informal economy, for the EU member states (including United Kingdom), between 2004-2020. Results show that both agricultural labor and rural population influence the informal economy. On the contrary, there is an indirect relationship between social benefits and the informal economy. In addition, some concluding suggestions for possible future research areas are proposed.